How Does Green Marketing Strategy of Micro, Small and Medium Enterprises Influence on Consumer Behaviour? - Sathana, V. (Rajarata University of Sri Lanka, 2021)
Health issues and environmental pollution draw consumers towards green products and services. These issues have also been crushed the peace of the world. They are small in their size and they have been struggling to improve their business. A significant number of manufacturing Micro, Small, and Medium Enterprises produce natural products and have more concern on green features. Green marketing information about the products of Micro, Small, and Medium Enterprises is poorly disseminated to the potential consumers, and the importance of green marketing is not proved for Micro, Small, and Medium Enterprises. The purpose of this research is to prove how green marketing strategy influences on the consumer behaviour of Micro, Small, and Medium Enterprises. This research applied quantitative research methodology and deductive research approach. The structured questionnaires were used to collect data from samples; the data were collected from 316 consumers of the manufacturing sector and the collected data were analyzed by using Structural Equation Modeling analysis. This study is built up with three dimensions of green marketing strategies as independent variables namely, eco-labeling, eco-brand, and environmental advertisement, and dependent variable namely, consumer purchase behaviour. The result shows that there is a strong positive influence of green marketing strategies on consumers’ purchase behaviour. This finding explains that better green marketing strategies and green marketing methods need to be used to change the purchase behaviour of customers and encourage them to consume more products from manufacturing Micro, Small, and Medium Enterprises. The finding also reveals that the green marketing strategies and consumer purchase behaviour are at the highest level among the consumers. Moreover, this study examines the effects of environmental advertisement, consumers’ perception of eco-label and impact of eco-brand on their actual purchase behaviour of green product of Micro, Small and Medium Enterprises; the result describes that the environmental advertisement, consumers’ perception of ecolabel and eco-brand are positive significant effect on the actual purchase behaviour of the green product. These findings ensure that green marketing features of Micro, Small, and Medium Enterprises are the prominent tool to influence the purchase behaviour of consumers and help to protect their healthiness. These findings also help to strengthen the Sri Lankan Manufacturing Micro, Small, and Medium Enterprises.
Keywords: Consumer behaviour; Eco-advertisement; Eco-brand; Eco-label; Green marketing